2017
DOI: 10.1371/journal.pone.0170966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of absorbent materials for use as ad hoc dry decontaminants during mass casualty incidents as part of the UK’s Initial Operational Response (IOR)

Abstract: The UK’s Initial Operational Response (IOR) is a revised process for the medical management of mass casualties potentially contaminated with hazardous materials. A critical element of the IOR is the introduction of immediate, on-scene disrobing and decontamination of casualties to limit the adverse health effects of exposure. Ad hoc cleansing of the skin with dry absorbent materials has previously been identified as a potential means of facilitating emergency decontamination. The purpose of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…In recent years, there has been some scepticism over the suitability of aqueous-based decontamination systems, due to the phenomenon of a "wash-in" effect that can enhance chemical penetration through the skin (Idson, 1978;Moody and Nadeau, 1997;Zhai, 2002). Studies comparing the effectiveness of washing the skin or using absorbent materials resulted in better efficacy when absorbent materials were employed (Amlôt, 2017;Kassouf, 2017;Lademann, 2011). A further reason for developing a sponge or textile formulation is to mitigate possible issues surrounding the use of powder decontaminants, such as methods of application to the skin, containment and clear-up, in light of the dispersive properties of powders as well as their potential to be ACCEPTED MANUSCRIPT…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been some scepticism over the suitability of aqueous-based decontamination systems, due to the phenomenon of a "wash-in" effect that can enhance chemical penetration through the skin (Idson, 1978;Moody and Nadeau, 1997;Zhai, 2002). Studies comparing the effectiveness of washing the skin or using absorbent materials resulted in better efficacy when absorbent materials were employed (Amlôt, 2017;Kassouf, 2017;Lademann, 2011). A further reason for developing a sponge or textile formulation is to mitigate possible issues surrounding the use of powder decontaminants, such as methods of application to the skin, containment and clear-up, in light of the dispersive properties of powders as well as their potential to be ACCEPTED MANUSCRIPT…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that a major route of exposure to chemical warfare (CW) agents is via contact with the skin (Evison, 2002). The deliberate release of chemical warfare agents targeting civilian populations, exemplified by the sarin attacks in Tokyo (1995) and Syria (2014) (Eisenkraft, 2014;Okumura, 1996), has led to the continued development of more effective decontamination strategies focused on dealing with civilian mass-casualty incidents (Amlot, 2010;Amlôt, 2017;Kassouf, 2017;Matar, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…83 In terms of wet versus dry decontamination, another study of absorbent materials in an ex vivo model indicated that dry decontamination was superior to wet methods for removing liquid contaminants but was not effective against particulate matter. 84 The consensus among investigators, however, is that time is the single most important factor in successful decontamination. 85 In most cases, decontamination is most successful if performed within minutes of exposure, which has the added benefit of mitigating the demand on health care facilities.…”
Section: Decontaminationmentioning
confidence: 99%
“…The most pragmatic option is to use any readily available (nonproprietary) absorbent material to treat exposure to noncaustic liquids, such as chemical warfare agents and toxic industrial chemicals (4). Recent work has identified a number of such materials (5,6). However, while the IOR represents a substantial improvement in the initial clinical management of ambulant casualties, there is currently no comparable protocol for nonambulant patients.…”
Section: Introductionmentioning
confidence: 99%